Reforming support policies to improve Chinese nutrition and diet - Zhao, Qiran; Zhang, Yumei; Fan, Shenggen; Chen, Kevin Z.; Yi, Cui; Zhang, Ying (2022)
On March 6, 2022, at the Fifth Session of the Thirteenth National Committee of the Chinese People’s Political Consultative Conference, Chinese President Xi Jinping emphasized that China needs to improve the lives and livelihoods of its people and to ensure an adequate food supply by providing enough meat, vegetables, fruit, and aquatic products for healthy diets. Understanding the changing trends of people’s dietary structure and encouraging people to eat more healthily is central to establishing the “Big Food” concept. The country should actively promote reform of the agricultural supply side in order to achieve a balance between the supply of, and demand for, various types of food and to better meet the increasingly diversified food consumption needs of the people.